(3EQTGO GdbGUO Edi CSfi GdebGUOs - (3eMeO Hf EHQGgje Hf SGYO GdGfUGQj GdSfLGQj, hjYQa HGHf GdCcaGfj, CHh YHO Gddg,J (B749 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb GdEfSGf haVdg Ydi SGFQ GdMjhGf aCQOJ Cf CPcQ ai gPg GdQSGdI CfhGY GdYdhe Ydi GdJaUjd s
(3BNQgG (B:s
(3Cf jfaYd (B: (3gh chf GdTF eJCKQkG Yf ZjQg , cGdG fbWGY , hgPg GdebhdGJ TGedI HLejY GdehLhOGJ GdeecfI hdjcf gPG BNQ GdcdGe ai gPg GdQSGdI MSHfG Gddg hfYe Gdhcjd s
(3HgG fXGe GdJYbjHIs
(3dYd GdbQGAI GdJi GbQFJ Ydi GdeDda ebhdg Yf fSNI GdCUd GdefJSN efgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B299 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B200s
(3JHUQGJ GdCUd (B:s
(3bQFJ Ydi GdeDda SfI (B726s
Keywords: (3GdeYGQa GdYGeIs